Classroom Management Applied By The Eighth Grade Teacher In Teaching English In SMP Muhammadiyah 1 Surakarta In 2012/2013 Academic Year - Palupi, Agata Retno; , Drs. H. Djoko Srijono, M.Hum; , Dra. Dwi Harjanti, M.Hum (2013)
This research paper aims at describing the classroom management applied by the eighth grade teacher in teaching English in SMP Muhammadiyah 1 Surakarta, to classify the factors influence the classroom management and interaction in the class, and to describe the problems faced by the eighth grade teacher in applying his classroom management in the class. The data will be analyzed using classroom management theory written by Prof. Dr. Endang Fauziati. This research applies descriptive research. In collecting data, the writer uses observation, interview, and analyzing document. The data were analyzed by (1) identifying the data found in the field (2) classifying the data found with the theory of classroom management proposed by Prof. Dr. Endang Fauziati (3) Interpreting the data to research finding (4) drawing the conclusion of classroom management research. The components of classroom management which are applied by the eighth grade teacher in SMP Muhammadiyah 1 Surakarta in teaching English are: 1) teacher talk 2) teacher talking time always gives opportunities to the students to ask some questions. 3) physical presence. 4) seating arrangement 5) element necessary in language classroom. Factors that influence the classroom management and interaction in the class are: 1) time allocation 2) seating arrangement. The problems faced by the eighth grade teacher in applying classroom management in the class are: 1) cleanliness 2) class discipline.